Application of the Reference Method Isotope Dilution Gas Chromatography Mass Spectrometry (ID/GC/MS) to Establish Metrological Traceability for Calibration and Control of Blood Glucose Test Systems. (May 2014) - Andreis, Elisabeth; Küllmer, Kai; Appel, Matthias
Self-monitoring of blood glucose (BG) by means of handheld BG systems is a cornerstone in diabetes therapy. The aim of this article is to describe a procedure with proven traceability for calibration and evaluation of BG systems to guarantee reliable BG measurements. Isotope dilution gas chromatography mass spectrometry (ID/GC/MS) is a method that fulfills all requirements to be used in a higher-order reference measurement procedure. However, this method is not applicable for routine measurements because of the time-consuming sample preparation. A hexokinase method with perchloric acid (PCA) sample pretreatment is used in a measurement procedure for such purposes. This method is directly linked to the ID/GC/MS method by calibration with a glucose solution that has an ID/GC/MS-determined target value. BG systems are calibrated with whole blood samples. The glucose levels in such samples are analyzed by this ID/GC/MS-linked hexokinase method to establish traceability to higher-order reference material. For method comparison, the glucose concentrations in 577 whole blood samples were measured using the PCA-hexokinase method and the ID/GC/MS method; this resulted in a mean deviation of 0.1%. The mean deviation between BG levels measured in >500 valid whole blood samples with BG systems and the ID/GC/MS was 1.1%. BG systems allow a reliable glucose measurement if a true reference measurement procedure, with a noninterrupted traceability chain using ID/GC/MS linked hexokinase method for calibration of BG systems, is implemented. Systems should be calibrated by means of a traceable and defined measurement procedure to avoid bias.